Pengaruh Kepemimpinan Transformasional dan Learning Organization Terhadap Kinerja Perguruan Tinggi Swasta di Surabaya - Yanti, Dyah Agustin Widhi (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2018)
The aim of this study is to examine and analyze the influence of transformational leadership and learning organization on the performance of private universities in Surabaya. The population in this study were all private university‘s leaders in Surabaya area. The sampling method uses census method, where all members of the population are made as research samples. Research Results: 1). Transformational leadership has no significant effect on organizational performance. The results of this study indicate that the application of transformational leadership does not guarantee that it can improve performance even though in transformational leadership the leader provides inspiration and motivation to lecturers and education personnel to achieve better results than planned, it does not affect organizational performance because organizational performance is determined by performance lecturers where the lecturers' work is independent rather than motivating themselves to carry out their own tasks without being influenced by their leaders and lack of communication between leaders and subordinates. 2). The results of this study found that Learning Organization has a significant effect on Organizational Performance. The findings in the field indicate that Learning Organization must be maintained and even increased by Higher Education organizations, because in these variables it is a factor that must be considered and implemented well in universities in achieving optimal performance given the achievement of important universities as a basis for obtaining accreditation and other university achievements.